REALITAS BAHASA TERHADAP BUDAYA SEBAGAI PENGUATAN LITERASI PENDIDIKAN - Effendi, Darwin; Wahidy, Achmad (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Language is a reflection of the reality of the activities of human life. As social beings, humans need communication. Activities can work well if communication goes well too. The facilities that facilitate it are language so that language influences the human mindset itself. A polite language is one a reflection of Indonesian culture that has been inherited from generation to generation. Therefore, language and culture are closely related. The expression of good language is also supported by a good understanding of literacy. The shifting of interpretations of reality in language expressions often occurs due to changes in the cultural values in life, community itself. The reality of language expressions in the context of culture and language is intended to clarify the meaning contained in several cultural problems through language analysis.